Experimental Investigation of Mechanical and Electromagnetic Performance of Asphalt Concrete Containing Different Ratios of Graphite Powder as a Filler to be Potentially Used as Part of Wireless Electric Roads - Orhan Kaya; Hatice Merve Annagur; Olcay Altintas (The Baltic Journal of Road and Bridge Engineering)
This study experimentally investigates the usability of asphalt concrete pavement containing five different ratios of graphite powder (0%, 1.25%, 2.5%, 3.75% and 5% by weight of the aggregate blend or 0%, 25%, 50%, 75% and 100% of the filler content) as a filler to be potentially used as part of wireless electric roads (ER). As part of the study, first, optimum asphalt binder content for the asphalt mixes without graphite powder was determined as 5%. Then, using the determined optimum asphalt binder content, asphalt mixes containing five different ratios of graphite powder as a filler were prepared and their mechanical and volumetric properties based on Marshall mix design methodology were evaluated. As graphite powder ratios in the asphalt mixes increased, their Marshall stability, flow, voids filled with asphalt and unit weight test results mostly decreased but their air content and voids in mineral aggregate test results increased. Possible reasons for this could be: (1) lower bulk specific gravity of graphite powder, (2) higher asphalt absorbance, (3) having greater surface area compared to that of limestone filler, and (4) weak bonds between sheet-like graphite layers. Furthermore, another batch of asphalt mixes containing five different ratios of graphite powder were prepared and tested in the frequency range of 3–18 GHz for their electromagnetic permittivity properties. It was observed in this study that, except for the specimens with 100% graphite powder ratios, transmission magnitudes of all specimens were above 50% up to 8 GHz, indicating that they had comparably high transmission magnitudes so as comparably low tangent loss values. In the frequency range of 3–13 GHz, transmission magnitudes of the specimens with 25% and 50% graphite powder ratios were consistently higher than that having no graphite powder, the ones with 25% powder ratios had the highest transmission magnitudes in most of the cases in this frequency range. Considering the mechanical, volumetric and electromagnetic property test results of the asphalt mixes with five different ratios of graphite powder, it can be concluded that the use of 25% graphite powder ratio (corresponding to 1.25% of the aggregate blend used in the mixes), has a comparably lower negative effect on mechanical and volumetric properties of asphalt mixes and has a positive effect on electromagnetic permittivity properties of asphalt mixes. Asphalt mixes produced with this graphite powder ratio can be considered to be used as part of wireless ER.